![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)?32+(?12)?2?(?13)0;(2)(-12x4y3)÷(2x2y)2?(-3xy)(3)(15x3y5-10x4y4-20x3y2)÷
计算:(1)?32+(?12)?2?(?13)0;(2)(-12x4y3)÷(2x2y)2?(-3xy)(3)(15x3y5-10x4y4-20x3y2)÷(-5x3y2...
计算:(1)?32+(?12)?2?(?13)0;(2)(-12x4y3)÷(2x2y)2?(-3xy)(3)(15x3y5-10x4y4-20x3y2)÷(-5x3y2)
展开
1个回答
展开全部
(1)原式=-9+4-1=-6
(2)原式=(-12x4y3)÷(4x2×2y2)?(-3xy)
=(-3x0y)?(-3xy)
=9xy2
(3)原式=[15x3y5÷(-5x3y2)]+[(-10x4y4)÷(-5x3y2)]+[(-20x3y2)÷(-5x3y2)]
=-3y3+2xy2+4.
(2)原式=(-12x4y3)÷(4x2×2y2)?(-3xy)
=(-3x0y)?(-3xy)
=9xy2
(3)原式=[15x3y5÷(-5x3y2)]+[(-10x4y4)÷(-5x3y2)]+[(-20x3y2)÷(-5x3y2)]
=-3y3+2xy2+4.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询